VD_FINDINFO ML / 2020 / 107 vom 15. Mai 2020 - VD Tribunal cantonal (2020)
MAINLEVÉE DÉFINITIVE, TITRE DE MAINLEVÉE, SURSIS AU PAIEMENT, CONCORDANCE, CRÉANCE, EXIGIBILITÉ | 80 al. 2 ch. 2 LP, 80 LP, 81 al. 1 LP